Evaluation of xylanase production by a thermophillic fungus Thermoascus aurantiacus SL16W using statistic experimental designs and the arabinose inductive effect - Niwat Chawachart (2018)
Different compositions of supplements, carbon and nitrogen sources were investigated to find the optimum solid substrate media for xylanase production using isolated Thermoascus aurantiacus SL16W cultured at 45°C. Corncob, ammonium dihydrogen phosphate and soybean meal were selected as the carbon source, inorganic nitrogen source and supplementary organic nitrogen source, respectively, for xylanase production using solid substrate fermentation. Applying factorial design to screen the nutritional factors affecting on xylanase production found that corncob and soybean meal were significant factors (P > 0.05). Central composite design (CCD) were applied to optimize media composition and the optimum medium composition predicted by response surface methodology (RSM) was 1.27 g corncob, 1.32 g soybean meal, 0.04 g ammonium dihydrogen phosphate and 50% (w/w) initial moisture content. The maximum value of xylanase activity predicted by the model was 6,377±198 U g -1 substrate. Addition 0.5% (w/w) either of L-arabinose and lactose demonstrated an inductive effect on xylanase production in solid substrate fermentation and increased the enzyme activity up to 8547±184 and 7655±187 U g -1 substrate, respectively.